Quality Improvements in a Leading Eye Care Company - Learning from Six Sigma? - Sennerdal, Ola (My University, 2006)
The Cataract Operations area in a leading eye care company is facing problems with decreasing the defects per unit for the manufacturing of its surgical instruments. The company s current methodology of solving problems and decreasing the number of defects (Six Step Problem Solving Process) is in need of improvements. The main purpose of this thesis is to investigate if the methodology of Six Sigma and/or Design for Six Sigma can reveal improvements for the current problem solving procedure at a leading company in eye care products. To carry out this thesis and fulfil its purpose, a case study and a theory study have been conducted. The practical part of the methodology consists of taking on one of the biggest mechanical problems in this Cataract Operations area at a leading eye care company and trying to solve it with the company s procedure. The theoretical part is made up by a literature review of Six Sigma and Design for Six Sigma. Using Six Sigma as a model, improvement potentials for the Six Step Problem Solving Process could be found and suggested improvements could be given. The results explain that the Six Step Problem Solving Process used at the Cataract Operations area misses parts of the framework and methodology that the strategy of Six Sigma strives for. Training, the measurement system, and supplier and employee involvement for this process can be improved. The methodology steps and the associated toolbox used to solve problems also need advancements necessary to solve various types of problems. These improvement potentials can be realized with the help of Six Sigma. Four different suggestions of how to implement these improvement potentials for the Six Step Problem Solving Process are given.
Keywords: Industriell teknik och ekonomi; Hälso- och sjukvårdsorganisation, hälsopolitik och hälsoekonomi; Industrial engineering and economy; Health Care Service and Management, Health Policy and Services and Health Economy